2017
DOI: 10.1016/j.topol.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Small loop transfer spaces with respect to subgroups of fundamental groups

Abstract: Let H be a subgroup of π 1 (X, x 0 ). In this paper, we extend the concept of X being SLT space to H-SLT space at x 0 . First, we show that the fibers of the endpoint projection p H :X H → X are topological group when X is H-SLT space at x 0 and H is a normal subgroup. Also, we show that under these conditions the concepts of homotopically path Hausdorff relative to H and homotopically Hausdorff relative to H coincide. Moreover, among other things, we show that the endpoint projection map p H has the unique pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Let p : X → X be an lpc 0 -covering map with p * π 1 ( X,x 0 ) = H. In [4, Lemma 5.10] it was shown that p is equivalent to the endpoint projection map p H : X wh H → X. Moreover, it was shown that the fiber p −1 (x 0 ) is Hausdorff and hence (p −1 H (x 0 )) wh is Hausdorff (see [13,Corollary 3.10]). On the other hand, since |p −1 (x 0 )| < ∞, we have…”
Section: Relationship Between Strong Slt Spaces and Covering Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let p : X → X be an lpc 0 -covering map with p * π 1 ( X,x 0 ) = H. In [4, Lemma 5.10] it was shown that p is equivalent to the endpoint projection map p H : X wh H → X. Moreover, it was shown that the fiber p −1 (x 0 ) is Hausdorff and hence (p −1 H (x 0 )) wh is Hausdorff (see [13,Corollary 3.10]). On the other hand, since |p −1 (x 0 )| < ∞, we have…”
Section: Relationship Between Strong Slt Spaces and Covering Mapsmentioning
confidence: 99%
“…Also, note that the example below shows that the concepts of relative version of strong SLT and SLT spaces are not necessarily the same. (HE, x 0 ), Proposition 3.6 of [13] implies that HE is an H-SLT space at x 0 and hence, using [13,Proposition 3.7], H is an open subgroup of π wh 1 (X, x 0 ). One can see that H is not an open subgroup in π l 1 (HE, x 0 ) because it is not a covering subgroup.…”
Section: Relationship Between Open Subsets Of π Whmentioning
confidence: 99%
“…In [6, Theorem 4.12] Brodskiy et al showed that this coincidence holds at all point x ∈ X when X is a locally path connected SLT space. Moreover, Pashaei et al [12] showed that the property of being SLT at x 0 for the space X is a necessary and sufficient condition for the coincidence π wh 1 (X, x 0 ) = π qtop 1 (X, x 0 ). In the following theorem, using path Spanier groups, we give another proof for this statement.…”
Section: On the Whisker Topology And Sltl Spacesmentioning
confidence: 99%
“…In this paper, we are going to investigate on the relationship between the topological group property of π wh 1 (X, x 0 ) and π qtop 1 (X, x 0 ) and SLT spaces at one point which are introduced in [12]. In Section 2, first, we address to the relationship between path Spanier groups, introduced in [14], and SLT spaces at a point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation